(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Postpartum depression (PPD) affects about 15% of mothers. It is a serious disorder that may affect physical and mental health of new mothers and newborns. Mothers suffering from anemia and vitamin D deficiency may be at increased risk of developing PPD. Aim: Our study aimed to detect the association of anaemia and Vit D deficiency with postpartum depression & also to look at association of other maternal and perinatal complications. Materials & methods: In this cross sectional observational study, pregnant women having anemia (Hb% <11gm/dl), were grouped as A (n=141), pregnant women having low Vit D were grouped as B (n=28), and pregnant women with normal Hb% and normal Vit D were grouped as grouped C (n=58). A & B were taken as cases and group C was taken as control in the study. Depression was evaluated by using Edinburg postnatal depression rating scale, P <0.05 was taken as statistically significant. Also secondary outcome like PPH, wound infection, Apgar score, preterm birth neonatal admission were noted down. Results: Depression was found significantly higher in both A= 60.3% and B =14.2%, than group C =0% (p<0.0001). Postpartum hemorrhage (PPH) and wound infection were found higher for group A (58% & 13%), Group B (28 &3%) respectively than control group C (5 &2%). Interestingly all women with VitD deficiency had postpartal haemorrhage (PPH). Regarding neonatal outcome, APGAR score was low in A (38%) and B (10.7%) in compare to control group C (0%). NICU Admission was seen higher in A=26% & B=10.7% than for C=0%. Incidence of Preterm birth (PTB) for A =25% & B= 2% were significantly higher than group C= 0%. No stillbirth was found in any group. Conclusion: Prevention, identification and treatment of anaemia and Vitamin D deficiency in pregnant women seem necessary, as they are strongly associated with postpartum depression and other complications. J Bangladesh Coll Phys Surg 2023; 41: 114-119